CAR-T and other adoptive cell therapies for B cell malignancies - Peihua Lu (Elsevier, 2021)
B cell malignancies pose challenges due to therapeutic resistance and repeated relapse. Advances in adoptive cellular therapies including chimeric antigen receptor (CAR)-T cells have the potential to transform the treatment landscape in hematological and solid tumor cancers. Improvements in constructs of CAR-T have improved specificity in targeting malignant cells. Multiple clinical trials have demonstrated the efficacy of CAR-T and other cellular treatments. In spite of advances in cellular therapies, hurdles in managing toxicities and lingering resistance remain. This review aims to summarize current innovations in adoptive cellular therapies and introduces future paths of discovery that will enhance these therapies in the era of precision oncology.